2013
DOI: 10.1186/1478-811x-11-26
|View full text |Cite
|
Sign up to set email alerts
|

The Lnk/SH2B adaptor provides a fail-safe mechanism to establish the Insulin receptor-Chico interaction

Abstract: BackgroundInsulin/insulin-like growth factor signalling (IIS) has been described as one of the major pathways involved in growth control and homeostasis in multicellular organisms. Whereas its core components are well established, less is known about the molecular functions of IIS regulators. The adaptor molecule Lnk/SH2B has been implicated in IIS but the mechanism by which it promotes IIS activity has remained enigmatic.ResultsIn this study, we analyse genetic and physical interactions among InR, Chico and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…X11L has been implicated in amyloid precursor protein (APP) regulation in both Drosophila and mammalian cells (Hase et al 2002;Gross et al 2008), with no reported connections to either Jak/Stat or tyrosine kinase signaling. Lnk negatively feeds back on Jak/Stat signaling in mammalian cells, although in Drosophila it has been studied as a positive regulator of insulin/insulin-like growth factor signaling (Werz et al 2009;Oh et al 2010;Slack et al 2010;Almudi et al 2013). The Jak/Stat ligands unpaired (Upd) 2 and 3 influence insulin signaling in Drosophila (Rajan and Perrimon 2012; Woodcock et al 2015), thus potentially implicating Lnk in Jak/Stat signaling in flies.…”
Section: Resultsmentioning
confidence: 99%
“…X11L has been implicated in amyloid precursor protein (APP) regulation in both Drosophila and mammalian cells (Hase et al 2002;Gross et al 2008), with no reported connections to either Jak/Stat or tyrosine kinase signaling. Lnk negatively feeds back on Jak/Stat signaling in mammalian cells, although in Drosophila it has been studied as a positive regulator of insulin/insulin-like growth factor signaling (Werz et al 2009;Oh et al 2010;Slack et al 2010;Almudi et al 2013). The Jak/Stat ligands unpaired (Upd) 2 and 3 influence insulin signaling in Drosophila (Rajan and Perrimon 2012; Woodcock et al 2015), thus potentially implicating Lnk in Jak/Stat signaling in flies.…”
Section: Resultsmentioning
confidence: 99%
“…Almudi et al [128] showed that Drosophila SH2B binds to both Chico and insulin receptors in Drosophila cells. SH2B-deficient flies display defects in insulin/IGF signaling, developmental delay, small size, and female sterility [4,5] .…”
Section: Metabolic Function Of Sh2b1 Is Evolutionarily Conservedmentioning
confidence: 99%
“…The C-terminal tail has SH3sites that recruit Dock to direct axon guidance, and SH2-sites that recruit Chico to regulate growth (89). At the InR N-terminal juxtamembrane domain, SH2B sites recruit Lnk to modulate interaction with Chico, and mutation of lnk extends lifespan (90)(91)(92)(93). Based on these facts, we…”
Section: Inr 353(hr) : Kinase Insert Domainmentioning
confidence: 92%